VYUŽITÍ STANOVENÍ PROKALCITONINU V DIAGNÓZE A PROGNÓZE SEPTICKÝCH STAVŮ. - Pavlíková, Lenka (Jihočeská univerzita, 2010)
The Master thesis gives an overview of sepsis, its causes, manifestation and diagnostics. The role of procalcitonin as a sepsis marker is dicussed. In the experimental part, case records of 106 were examined and the determination of procalcitonin as a sepsis marker was evaluated. Based on the evaluation, a recommendation about timing of the procalcitonin level analyses with septic patients were made.
Use of Procalcitonin Levels Measurement in Diagnosis and Prognosis of Septic States.
Keywords: prokalcitonin; sepse; procalcitonin; sepsis